Comprehensive analysis of brain injury parameters in a preclinical porcine model of acute liver failure - Felgendreff, Philipp; Hosseiniasl, Seyed M.; Felgendreff, Lisa; Amiot, Bruce P.; Minshew, Anna; Ahmadzada, Boyukkhanim; Qu, Zhi; Wilken, Silvana; Arribas Gomez, Ines; Nyberg, Scott L.; Cook, Casey N. (Frontiers in Medicine, 2024)
Acute liver failure (ALF) is defined as acute loss of liver function leading to hepatic encephalopathy associated with a high risk of patient death. Brain injury markers in serum and tissue can help detect and monitor ALF-associated brain injury. This study compares different brain injury parameters in plasma and tissue along with the progression of ALF.ALF was induced by performing an 85% liver resection. Following the resection, animals were recovered and monitored for up to 48hr or until reaching the predefined endpoint receiving standard medical therapy (SMT). Blood and serum samples were taken at Tbaseline, T24 and upon reaching endpoint (Tend). Control animals were euthanized by exsanguination following plasma sampling. Postmortem brain tissue samples were collected from the frontal cortex (FCTx) and cerebellum (Cb) of all animals. GFAP and tau protein and mRNA levels were quantified by ELISA and qRT-PCR in all plasma and brain samples. Plasma neurofilament light (NFL) was also measured by ELISA.All ALF animals (n=4) were euthanized upon showing signs of brain herniation. Evaluation of brain injury biomarkers revealed that GFAP was elevated in ALF animals at T24hr and Tend, while Tau and NFL concentrations were unchanged. Moreover, plasma glial fibrillary acidic protein (GFAP) levels were negatively correlated with total protein, and positively correlated with both aspartate transaminase (AST) and alkaline phosphatase (AP). Additionally, lower GFAP and tau RNA expression was observed in the ALF group in the FCTx but not in the CB tissue.The current large animal study identified a strong correlation between GFAP concentration in the blood and markers of ALF. Additionally, the protein and gene expression analysis in the FCTx revealed that this area appears to be susceptible while the CB is protected from the detrimental impacts of ALF-associated brain swelling. These results warrant further studies to investigate the mechanisms behind this process.